2007
DOI: 10.1073/pnas.0608056104
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between chromatin proteins MECP2 and ATRX is disrupted by mutations that cause inherited mental retardation

Abstract: Mutations in the human methyl-CpG-binding protein gene MECP2 cause the neurological disorder Rett syndrome and some cases of X-linked mental retardation (XLMR). We report that MeCP2 interacts with ATRX, a SWI2/SNF2 DNA helicase/ATPase that is mutated in ATRX syndrome (␣-thalassemia/mental retardation, X-linked). MeCP2 can recruit the helicase domain of ATRX to heterochromatic foci in living mouse cells in a DNA methylation-dependent manner. Also, ATRX localization is disrupted in neurons of Mecp2-null mice. Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
201
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(210 citation statements)
references
References 53 publications
8
201
1
Order By: Relevance
“…19 Interestingly, both the N-terminal ATRX-Dnmt3-Dnmt3L (ADD) domain and the C-terminal ATPase/helicase domain of ATRX modulated the dynamics of pericentromeric heterochromatin by increasing H3K9me3 levels at its target loci and ultimately, to nuclear damage in striatal cells. 15 These findings suggest that ATRX facilitates the pathological heterochromatin condensation and triggers the cascade of events leading to neuronal degeneration. 12 A recent study confirms that the ADD domain of ATRX interacts with histone H3 tails that are trimethylated at lysine 9.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…19 Interestingly, both the N-terminal ATRX-Dnmt3-Dnmt3L (ADD) domain and the C-terminal ATPase/helicase domain of ATRX modulated the dynamics of pericentromeric heterochromatin by increasing H3K9me3 levels at its target loci and ultimately, to nuclear damage in striatal cells. 15 These findings suggest that ATRX facilitates the pathological heterochromatin condensation and triggers the cascade of events leading to neuronal degeneration. 12 A recent study confirms that the ADD domain of ATRX interacts with histone H3 tails that are trimethylated at lysine 9.…”
Section: Discussionmentioning
confidence: 92%
“…12 ATRX collaborates with methyl-CpG-binding protein 2 and Daxx and disruption of these interactions may cause transcriptional deregulation and pathological changes that contribute to mental retardation. [13][14][15] In addition, the loss of ATRX leads to genomic instability and impaired corticogenesis. 11,16 ATRX is an epigenetic modulator necessary for cell survival during early neuronal differentiation and its abnormal induction or deficiency leads to neuronal degeneration, but the mechanisms responsible are largely unknown.…”
mentioning
confidence: 99%
“…Specifically, evidence now exists that ATRX might target chromatin directly through GATA-1-like domain interactions with the DNA template (Cardoso et al, 2000;Law et al, 2010). Alternatively, ATRX might associate with target chromatin through binding interactions with core/canonical and/or variant histone proteins, or through interactions with specific histone posttranslational modifications, either directly, or in combination with its interacting proteins HP1 (Kourmouli et al, 2005) or MeCP2 (Nan et al, 2007). It was recently demonstrated that the ADD domain of ATRX is able to efficiently bind H3K9me3 (a known heterochromatic mark) specific peptides in the absence of H3K4me3/2, due to an inability of the ATRX PHD finger domain to recognize and bind H3K4me3 (Dhayalan et al, 2011;Eustermann et al, 2011;Iwase et al, 2011).…”
Section: Atrx: a Critical Regulator Of Chromatin State And Histone Dymentioning
confidence: 99%
“…The C-terminus of ATRX contains seven conserved collinear domains conferring its ATPase activity, and other regions are important for mediating its protein-protein interactions and subnuclear localization (Bérubé, 2011) (see Figure 2 for detailed ATRX domain structure). ATRX is generally associated with repressive chromatin and has been shown to directly interact with the polycomb group protein EZH2 (Cardoso et al, 1998), the methyl-CpG-binding protein MeCP2 (Nan et al, 2007), and the heterochromatinassociated protein HP1alpha (Bérubé et al, 2000;Lechner et al, 2005). In most cell types, ATRX exclusively resides within the nucleus and tends to localize to highly repetitive sequences throughout the genome (eg, pericentromeric satellite sequences, ribosomal DNA, telomeres, etc) (McDowell et al, 1999;Law et al, 2010).…”
Section: Atrx: a Critical Regulator Of Chromatin State And Histone Dymentioning
confidence: 99%
“…9 ATRX interacts with MECP2 in vitro and colocalizes at pericentromeric heterochromatin in mature neurons of the mouse brain. 10 Recently, it was reported that ATRX, MECP2 and cohesin cooperate to silence a subset of imprinted genes in the postnatal mouse brain. 11 Those experimental findings suggest that abnormally expressed ATRX with MECP2 through their simultaneous duplications may modify the phenotypes usually observed in MECP2 duplication syndrome.…”
mentioning
confidence: 99%